Tris(2-Pyridylmethylamine)V(O)2 Complexes as Counter Ions of Diprotonated Decavanadate Anion: Potential Antineoplastic Activity - Corona-Motolinia, Nidia D.; Martínez-Valencia, Beatriz; Noriega, Lisset; Sánchez-Gaytán, Brenda L.; Melendez, Francisco J.; García-García, Amalia; Choquesillo-Lazarte, Duane; Rodríguez-Diéguez, Antonio; Castro, María Eugenia; González-Vergara, Enrique (Frontiers in Chemistry, 2022)
The synthesis and theoretical-experimental characterization of a novel diprotanated decavanadate is presented here due to our search for novel anticancer metallodrugs. Tris(2-pyridylmethyl)amine (TPMA), which is also known to have anticancer activity in osteosarcoma cell lines, was introduced as a possible cationic species that could act as a counterpart for the decavanadate anion. However, the isolated compound contains the previously reported vanadium (V) dioxido-tpma moieties, and the decavanadate anion appears to be diprotonated. The structural characterization of the compound was performed by infrared spectroscopy and single-crystal X-ray diffraction. In addition, DFT calculations were used to analyze the reactive sites involved in the donor-acceptor interactions from the molecular electrostatic potential maps. The level of theory mPW1PW91/6–31G(d)-LANL2DZ and ECP = LANL2DZ for the V atom was used. These insights about the compounds’ main interactions were supported by analyzing the noncovalent interactions utilizing the AIM and Hirshfeld surfaces approach. Molecular docking studies with small RNA fragments were used to assess the hypothesis that decavanadate’s anticancer activity could be attributed to its interaction with lncRNA molecules. Thus, a combination of three potentially beneficial components could be evaluated in various cancer cell lines.